PERANAN ANGGOTA KOPERASI BERKAH UMAT DALAM MENINGKATKAN MODAL DAN PENDAPATAN USAHA - Yeni Hendriyani (Lembaga P3M, 2022)
Abstract Islam as a religion that has been perfected, not only regulates matters of worship, but also issues muamalah. Al-Quran and Al-Hadith have a very universal reach and control whose texts are always appropriate to be applied in everyday life. Cooperative is an association or organization consisting of individuals or legal entities that work together to improve the welfare of members. To increase the capital and income of the cooperative business, it takes the role of each member of the cooperative itself because the main source of capital for the implementation of the cooperative business is derived from the basic, mandatory and voluntary savings of its members. To what extent is the role of members in increasing capital and income in the Berkah Ummah Cooperative, this is what this research wants to explore. The method used is descriptive qualitative research. The results obtained that the role of members of the cooperative is to make transactions and pay the deposits that have been determined. There is still a need for innovation and differentiation of cooperative programs so that the benefits of cooperatives can be felt by the community. Keywords: Role of members, capital, income. Abstrak Islam sebagai agama yang telah disempurnakan, bukan hanya mengatur masalah ibadah, melainkan juga masalah muamalah. Al Quran dan Al Hadits memiliki daya jangkau dan daya atur yang sangat universal yang teksnya selalu tepat untuk diaplikasikan dalam kehidupan sehari-hari. Koperasi adalah suatu perkumpulan atau organisasi yang beranggotakan orang-orang atau badan hukum yang bekerja sama untuk meningkatkan kesejahteraan anggota. Untuk meningkatkan modal dan pendapatan usaha koperasi, dibutuhkan peranan dari setiap anggota koperasi itu sendiri sebab sumber modal utama bagi pelaksanaan usaha koperasi yaitu berasal dari simpanan-simpanan pokok, wajib dan suka rela para anggotanya. Sampai sejauhmana peranan anggota terhadap peningkatan modal dan pendapatan dalam Koperasi Berkah Umat, ini yang ingin digali dalam penelitian ini. Metode yang digunakan adalah penelitian deskriptif kualitatif. Diperoleh hasil bahwa peran anggota terhadap koperasi adalah melakukan transaksi dan membayar simpanan yang telah ditetapkan. Masih diperlukan inovasi dan diferensiasi program koperasi agar kemanfaatan koperasi lebih dapat dirasakan oleh masyarakat. Kata Kunci : Peranan anggota, modal, pendapatan.